Understanding Proactive Personality, Knowledge Sharing, and Innovative Work Behavior in Knowledge-Intensive Firms - Tehreem Anjum; Farhan Sarwar (Journal of Applied Research and Multidisciplinary Studies, 2024)
The current study aimed to analyse the roles of innovative work behavior (IWB), knowledge sharing (KS), and proactive personality (PP) with gender as the moderator in organizations that are extensively dependent on knowledge. The current study was based on 522 employees of various organizations across different sectors, distinguished for their technical skills and knowledge intensity. The findings revealed rich understanding as to how these aspects underpin the process of innovation in organizations. Resultantly, the study demonstrated that people with proactive personalities directly affect both knowledge sharing (KS) and innovative work behavior (IWB). Self-starters can be defined by their initiative actions to solve problems before they arise. Moreover, they are proactive in contributing to the generation of new ideas within organizations. This behavior is effective to sustain such an environment where change and innovation are key development for competitive knowledge-intensive organizations.The current study also revealed that KS is a significant mediator in the relationship between PP and IWB. Although, this study has shown that a PP is optimal for creative work, this benefit is further boosted and compounded when knowledge is transferred amongst employees. This mediation effect indicates that KS would work synergistically with the proactive actions to enhance innovative capacities in order to generate enhanced innovation results in the organization. One of the interesting issues addressed by the study was the moderating influence of gender prevalent among these issues. This implies that the relationship between PP, KS, and IWB is moderated by gender which supports previous claims. This indicates that intervention type activities within organizations that are geared towards fostering innovation and knowledge management should take the gender factor into consideration for better results. The successful application of these strategies, when informed by gender, may help in holding efforts towards promoting a culture of innovation. One of the main strengths of the current study was that it awarded much of its attention to a singular field, however, it might weaken the transfer-ability of the results to other fields. Some aspects of the presented hypotheses could be more appropriate for knowledge- intensive organizations than for other forms of businesses, since the latter reveal certain peculiarities, which limits the generalisability of the results. Thirdly, conversely, though the participants’ total count was 522, it may also be significant. However, it may also be a source of bias if the provided sample does not reflect all the spectrum and specifics of the target population.